A Case Study on Software Aging in LLM-Generated Python Applications - Costa, Gustavo; Santos, Cesar; Natella, Roberto; Andrade, Ermeson (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2026: Anais do XXVII Workshop de Testes e Tolerância a Falhas, 2026)
Large Language Models (LLMs) have increasingly been used to automatically generate software systems. However, the long-term operational behavior of these applications remains poorly understood. In particular, it is still unclear whether LLM-generated systems may exhibit progressive performance degradation and increasing resource consumption over time, characterizing symptoms of software aging during prolonged execution. This work presents an experimental case study investigating possible aging effects in four Python applications generated with ChatGPT based on scenarios from the BaxBench benchmark. The systems were executed under continuous workload while memory consumption and response time were monitored. Statistical analyses using the Mann-Kendall test and Sen’s slope estimator were applied to detect temporal trends in the collected data. The results indicate consistent growth in memory consumption across the evaluated applications, suggesting evidence of aging, while response time degradation was observed in only one case.